Generation Z’s Digital Civic Engagement and Welfare-Oriented Participation: Evidence from an Indonesian University - Tengku Irmayani; Lina Sudarwati; Rio Sinaga (Women, Education, and Social Welfare, 2026)
Generation Z students increasingly encounter public issues through digital media, yet the extent to which awareness becomes sustained civic and welfare-oriented participation remains unclear. This study maps media use, information trust, welfare concern, and political participation among 922 students aged 17–25 years at the University of North Sumatra, Indonesia. A descriptive cross-sectional survey was complemented by short semi-structured interview notes used only for contextual interpretation. Social media was the most frequently used source of socio-political information (78.2%) and the most trusted source (48.9%), while official government websites retained substantial trust (39.6%). Education and health were the most frequently accessed public-interest topics (53.7% each), followed by economic issues (51.0%). Fundraising was the most common welfare-oriented action (49.1%), but only 26.4% reported regular social participation. Voting was reported by 66.5% of respondents; in contrast, direct roles in political parties or campaigns were uncommon. The findings identify a concern-to-participation gap: students are digitally connected, welfare attentive, and communicatively engaged, but their engagement is episodic and weakly institutionalized. Universities should combine critical digital literacy, service-learning, student-led welfare projects, and safe deliberative spaces to convert issue awareness into sustained democratic participation.